Nalar Ijtihad Peradilan: Membedah Garansi Teologis Hadis Nabi atas Posisi Hakim Kontemporer Melawan Kekosongan Hukum - Dwi Rezki Wahyuni; Muhammadiyah Amin; Abdul Rahman Sakka (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
Legal voids or the lack of written regulations nowadays often cause judges to face difficult legal dilemmas. Judges are not permitted to refuse cases, but they also face psychological and theological pressures when making new rulings. This article discusses the concept of ijtihad in the courts by examining the theological guarantees found in the Hadith of Prophet Muhammad SAW regarding the reward for judges who exercise ijtihad. This research employs a normative qualitative method with Hadith studies (content analysis) and takhrij, as well as analysing the main narrations from Amr bin al-Ash. The results indicate that the reward of twofold for correct ijtihad and onefold for incorrect ijtihad is a way to avoid criminalising unintentional legal errors. These theological guarantees help reduce judges' psychological pressure and encourage progress in legal discovery (rechtsvinding). However, these guarantees only apply to judges who meet methodological requirements and possess high moral integrity to prevent malpractice in the court.